Evaluation of the in vivo anti-inflammatory activity of a flavone glycoside from Cancrinia discoidea (Ledeb.) Poljak - Li, Qing-Chan; Su, Jian-Yu; Zhu, Liang (Technische Universität Dortmund, 2011)
The anti-inflammatory effect of selagin-7-O-(6″-O-Acetyl-)-β-D-glucoside, isolated from the medicinal herb Cancrinia discoidea (Ledeb.) Poljak, was evaluated for its anti-inflammatory activity in the carrageenin- and serotonin-induced rat paw oedema models of acute inflammation and the cotton pellet-induced granuloma rat model of chronic inflammation. Flavone glycoside at doses of 5, 10, or 20 mg/kg, the clinical anti-inflammatory indo-methacin at 10 mg/kg, or vehicle were administered orally before injection of the pro-inflammatory compound. The test compound showed significant anti-inflammatory activity against paw edema induced by carrageenin or serotonin, most notably at the highest test dose of 20 mg/kg. In the cotton pellet-induced granuloma model, the compound showed dose-dependent anti-inflammatory activity, with the highest effect at 20 mg/kg. In all three assays, the flavone glucoside compound was more active at 20 mg/kg than indomethacin at 10 mg/kg.
EXCLI Journal ; Vol. 10, 2011
Keywords: anti-inflammatory activity; Cancrinia discoidea (Ledeb.) Poljak; selagin-7-O-(6″-O-Acetyl-)-β-D-glucoside; 610